Polymorphisms in Human Soluble Epoxide Hydrolase - Przybyla-Zawislak, Beata D; Srivastava, Punit K; Vázquez-Matías, Johana; Mohrenweiser, Harvey W; Maxwell, Joseph E; Hammock, Bruce D; Bradbury, J. Alyce; Enayetallah, Ahmed E; Zeldin, Darryl C; Grant, David F (Molecular pharmacology, 2003)
Human soluble epoxide hydrolase (hsEH) metabolizes a variety of epoxides to the corresponding vicinal diols. Arachidonic and linoleic acid epoxides are thought to be endogenous substrates for hsEH. Enzyme activity in humans shows high interindividual variation (e.g., 500-fold in liver) suggesting the existence of regulatory and/or structural gene polymorphisms. We resequenced each of the 19 exons of the hsEH gene (EPHX2) from 72 persons representing black, Asian, and white populations. A variety of polymorphisms was found, six of which result in amino acid substitutions. Amino acid variants were localized on the crystal structure of the mouse sEH, resulting in the prediction that at least two of these (Arg287Gln and Arg103Cys) might significantly affect enzyme function. The six variants of the hsEH cDNA corresponding to each single polymorphism and one corresponding to a double polymorphism were then constructed by site-directed mutagenesis and expressed in insect cells. As predicted, Arg287Gln and the double mutant Arg287Gln/Arg103Cys showed decreased enzyme activity using trans-stilbene oxide, trans-diphenylpropene oxide, and 14,15-epoxyeicosatrienoic acid as substrates. Lys55Arg and Cys154Tyr mutants had elevated activity for all three substrates. Detailed kinetic studies revealed that the double mutant Arg287Gln/Arg103Cys showed significant differences in Km and Vmax. In addition, stability studies showed that the double mutant was less stable than wild-type protein when incubated at 37°C. These results suggest that at least six hsEH variants exist in the human population and that at least four of these may influence hsEH-mediated metabolism of exogenous and endogenous epoxide substrates in vivo.